2021
DOI: 10.1016/j.ensci.2021.100340
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID seizure: A new feature of “long-COVID”

Abstract: Novel coronavirus SARS-CoV-2 has created unprecedented healthcare challenges. Neurologic deficits are often an important presenting symptom. To date, the only reported post-infectious COVID-19 manifestations of neurologic disease include cognitive deficits and dysfunction of the peripheral nervous system. Here we report that seizure can also be a post-COVID-19 or “long-COVID” complication. We present a 71-year-old man with hypertension, diabetes mellitus, and COVID-19 diagnosed by RT-PCR who initially presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
0
11
0
2
Order By: Relevance
“…In some circumstances, the neurological problems may develop from the combination of them [ 19 ]. Although no direct link has been established, multiple cases have been reported regarding the association of SARS-CoV2 with chronic CNS disorders such as neurodegenerative disorders, multiple sclerosis, acute flaccid paralysis, Guillain barre syndrome, transverse myelitis and seizure [ 7 , [20] , [21] , [22] , [23] ]. The current study reported cases of Guillain barre syndrome, vascular dementia, seizure, and transient ischemic attack.…”
Section: Discussionmentioning
confidence: 99%
“…In some circumstances, the neurological problems may develop from the combination of them [ 19 ]. Although no direct link has been established, multiple cases have been reported regarding the association of SARS-CoV2 with chronic CNS disorders such as neurodegenerative disorders, multiple sclerosis, acute flaccid paralysis, Guillain barre syndrome, transverse myelitis and seizure [ 7 , [20] , [21] , [22] , [23] ]. The current study reported cases of Guillain barre syndrome, vascular dementia, seizure, and transient ischemic attack.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxie, Multiorganversagen und Stoffwechselstörungen, die typischerweise bei schweren Erkrankungen auftreten, wurden als zugrunde liegende Ursache vorgeschlagen. Ein kürzlich veröffentlichter Fall zu epileptischen Anfällen mit Long-COVID bei einem 71-jährigen männlichen Patienten, der negativ auf SARS-CoV‑2 war, ohne einem anderen aufgedeckten provozierenden Faktor, führte dazu, dass epileptische Anfälle in die Liste der Symptome von Long-COVID aufgenommen wurde [ 19 ].…”
Section: Neurologische Manifestationenunclassified
“…The proposed pathophysiology of these complications is associated with immune dysregulation, inflammation, microvascular thrombosis, iatrogenic effects of medications and psychosocial impacts of the infections (Nalbandian et al, 2021). Moriguchi et al, 2020Xiang et al, 2020Poyiadji et al, 2020Chakraborty et al, 2020Qi et al, 2020Emami et al, 2020 Nalbandian et al, 2021;Troyer et al, 2020Antonini et al, 2020Ferini-Strambi & Salsone, 2021Kincaid et al, 2021Helms et al, 2020 Neurological related disorders Further, neurological manifestations including encephalitis and stroke have a history of causing continuing consequences on the nervous system. There were few well-consolidated shreds of evidence linking COVID-19 to movement disorders, particularly for Parkinson's Disease (PD) (Antonini et al, 2020;Ferini-Strambi & Salsone, 2021).…”
Section: Neuropsychiatric Symptomsmentioning
confidence: 99%